2022
DOI: 10.13057/biodiv/d230951
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of mangrove forest and carbon stock estimation of east coast Surabaya, Indonesia

Abstract: Abstract. Hidayah Z, Rachman HA, As-Syakur AR. 2022. Mapping of mangrove forest and carbon stock estimation of east coast Surabaya, Indonesia. Biodiversitas 23: 4826-4837. The mangrove forests on Surabaya's east coast are an important protected area, providing habitat for a variety of marine organisms and water birds. This area is also vital for carbon storage and sequestration. The purpose of this research is to determine the changes in mangrove areas over the last 20 years and to calculate the amount of carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…The carbon stock in the mangrove forests of Benoa Bay Bali, however, is significantly lower when compared to natural mangrove forests in relatively undisturbed environments. Figure 4 compares carbon stocks from other locations in Indonesia and other Asian countries [3,20,21,[23][24][25][26][27][28]…”
Section: Figure 3 Results Of Agb Biomass and Carbon Stock Estimation ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The carbon stock in the mangrove forests of Benoa Bay Bali, however, is significantly lower when compared to natural mangrove forests in relatively undisturbed environments. Figure 4 compares carbon stocks from other locations in Indonesia and other Asian countries [3,20,21,[23][24][25][26][27][28]…”
Section: Figure 3 Results Of Agb Biomass and Carbon Stock Estimation ...mentioning
confidence: 99%
“…These coastal forests are highly efficient at capturing and storing carbon dioxide from the atmosphere, making them important carbon sinks. Studies have shown that mangrove carbon stocks vary across different regions and countries [3,34]. Global patterns indicate that mangrove carbon stocks are higher in the tropics compared to temperate regions.…”
Section: Image Processing and Agb Carbon Stock Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Kondisi ini dapat disebabkan oleh beberapa faktor seperti kegiatan akuakultur, pertanian, pembangunan perkotaan serta kegiatan antropogenik lainnya. Dengan laju deforestasi yang terus meningkat, menunjukkan perlu adanya informasi cepat, akurat dan terkini terkait kondisi mangrove (Anwar et al 2021;Hidayah et al 2022). Salah satunya mengenai sebaran dan perubahan luas vegetasi mangrove (Husnayaen et al 2023).…”
Section: Pendahuluanunclassified
“…They play a pivotal role in delivering a diverse set of benefits spanning ecological, social and economic benefits [1][2], including coastal protection from surges and waves, water filtration, a food source and nursery for fish and crustaceans, as well as a source of wood fuel, and opportunities for nature-based recreation [3][4][5][6]. Mangroves, being the only woody halophytes [7], have a crucial role in carbon storage within the context of climate change [8][9]. They are capable of storing organic carbon as sediment for extended periods and can also utilize carbon in the form of organic compounds [10][11].…”
Section: Introductionmentioning
confidence: 99%